The Potential of Sorghum Plants in Lamunde Village Tinondo District East Kolaka Regency - Kambuno, Grace Onela; Abdi, Abdi; Gafaruddin, Abdul (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2021)
Sorghum is one of the most important food crops globally, which has become the fifth food crop after wheat, rice, corn, and barley. Sorghum has excellent potential to be developed in Indonesia because it has wide adaptability, especially on dry land, and produces high productivity. This study aims to determine the possibility of sorghum plants in Lamunde Village, Tinondo District, East Kolaka Regency. The population in this study were sorghum farmers, totaling 25 people, using the method census or saturated sampling, which took the entire population as a sample so that 25 people were obtained as research samples. Data analysis used SWOT analysis using IFE (Internal Factors Evaluation) Matrix, EFE Matrix (External Factors Evaluation), and IE Matrix (Internal External). The results showed that the strategy that needs to be applied for sorghum farmers in seeing the potential for the development of sorghum plants in Lamunde Village is a strategy of concentration through vertical integration. Growth through engagement can be achieved through vertical integration by taking over the function of suppliers, namely sorghum farmers, or by taking over the tasks of distributors, namely buyers of sorghum production, either in the form of wholesalers or collectors and companies.